ANALYTICAL AND EXPERIMENTAL STUDY ON SURFACE TREATMENT FOR REINFORCED NORMAL CONCRETE - Mosleh Salman, Mohammed; Fadhil Hussein, Luma; Abdul Ghani Zghair, Luma (Journal of Engineering and Sustainable Development, 2020)
Applying some material such as Flunkout or sodium silicate on concrete surface has a great effect in enhancing the strength of concrete and eliminate the damage resulted from exposure to aggressive environments. Besides, it’s extended the service life of concrete. This research present a study on the effect of (Flunkout and sodium silicate) on the flexural behavior of 24 reinforced concrete beams with dimensions (100*100*900mm). Several variables were studied such as the type of surface treatment (Flunkout and sodium silicate), the method of curing (air and water curing) and the age of testing (30, 90, 180, and270days). In addition, the test result was compared with the normal specimens (without surface treatment). The test results showed that, by using surface treatment there is a noticeable enhancement in the concrete strength, also surface treatment affect mode of failure. In the second part of this study, an analytical study was done by using ANSYS (R.15). It was concluded that the results obtained from ANSYS models were underestimate the result of the study beams, however the maximum discrepancy in central deflection is found to be approximately (15.9%).